2004
DOI: 10.3139/146.017916
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative investigation of material erosion caused by high-pressure discharges in air and nitrogen

Abstract: Quantitative investigation of material erosion caused by high-pressure discharges in air and nitrogenSingle-spark erosion experiments were conducted in different pure metal samples. The samples were used as the cathode, and a platinum electrode was used as the anode. The sparks were produced at high pressure and room temperature, having at this conditions a breakdown phase (ca. 100 ns) and an arc phase (several hundreds of ls). The crater volumes on the different materials were correlated with several properti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 12 publications
2
21
0
Order By: Relevance
“…Lasagni et al [11] evaluated these three mechanisms and found that the erosion in single-spark experiments correlates well with the melting enthalpy. Hence, the particle ejection model seems to describe this process most suitably.…”
mentioning
confidence: 99%
“…Lasagni et al [11] evaluated these three mechanisms and found that the erosion in single-spark experiments correlates well with the melting enthalpy. Hence, the particle ejection model seems to describe this process most suitably.…”
mentioning
confidence: 99%
“…Reviewing similar experiments under gas atmosphere in metals basically two different kinds of erosion structures can be observed [3,4,15]. One representative is an erosion structure which has the typical form of a crater with a depth in the middle and rims of displaced materials at the sides.…”
Section: Discussionmentioning
confidence: 99%
“…This indicates that the energy input by ion bombardment and joule heating produces a melting of the material and the plasma forces acting on the molten silicon cause the displacement. According to Lasagni et al [4] the surface tension of the molten material plays an important role when the crater is formed. For relative low values of the surface tension like in aluminium (914 mN/m), tin (544 mN/m) and lead (468 mN/m), the craters exhibit the normal behaviour.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations